ANALISIS PENGARUH TINGKAT PENDIDIKAN DAN JENIS PEKERJAAN WAJIB PAJAK TERHADAP MOTIVASI DALAM MEMENUHI KEWAJIBAN PAJAK - -, Amilin; Yusronillah, Fanny (Jurnal Manajemen dan Keuangan, 2009)
The purpose of this research is to figure out the influence between education level and tax payers variety of jobs toward the motivation in fulfilling tax obligatory. The sample in this research includes 80 correspondences from 8 (eight) sub district of Jatinegara. Each sub district represents 10 correspondences. The sampling method is Area Sampling (cluster sampling). The collected of data to use primary data with questionnaire technique.Quality of test in this research are validity of test to use is Pearson correlation and reliability test of the research to use is cronbach alpha and then hypothesis test to use is Univariate analysis of variance (two way ANOVA). The results in this research are: (a). Educational level does not have any influences toward the motivation in fulfilling tax obligatory. (b). the variety of jobs it self does not have any influences towards the motivation in fulfilling tax obligatory. (c). the interaction between educational level and variety of jobs does not have any influences towards motivation in fulfilling tax obligatory.Keyword : Education level, variety of jobs, motivation to fulfilling tax obligatory.